2020
DOI: 10.21511/bbs.15(3).2020.03
|View full text |Cite
|
Sign up to set email alerts
|

Fintech in the eyes of Millennials and Generation Z (the financial behavior and Fintech perception)

Abstract: This study investigates the Millennials and Gen Z perception toward Fintech services, their usage intention, and their financial behavior. The study took place in the Palestinian context with a global comparison among these generations. The authors used the questionnaire-based technique to meet the study objective. West Bank respondents were selected for this purpose; the study instrument was distributed through different social media channels. The findings show that reliability/trust and ease of use are the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(30 citation statements)
references
References 13 publications
2
28
0
Order By: Relevance
“…(Interview 27,Zain) In line with the previous research, e-wallet is being used as a mode of transactions amongst youngsters, millennials, and generation Z altogether (Monilakshmane, 2019) (Daqar, 2020) (Persada, 2021). The main factors in using e-Wallet, namely discount (Prasasti, 2021); ease-of-use (Daqar, 2020); seemingly good idea (Persada, 2021); and the quality of mobile application (Phuong, 2020). In this study, the author found three striking answers from the interviewee.…”
Section: Interviewer: What Is the Reason Why You Used E-wallet During The Pandemics?supporting
confidence: 63%
See 1 more Smart Citation
“…(Interview 27,Zain) In line with the previous research, e-wallet is being used as a mode of transactions amongst youngsters, millennials, and generation Z altogether (Monilakshmane, 2019) (Daqar, 2020) (Persada, 2021). The main factors in using e-Wallet, namely discount (Prasasti, 2021); ease-of-use (Daqar, 2020); seemingly good idea (Persada, 2021); and the quality of mobile application (Phuong, 2020). In this study, the author found three striking answers from the interviewee.…”
Section: Interviewer: What Is the Reason Why You Used E-wallet During The Pandemics?supporting
confidence: 63%
“…(Interview 53,Karunia Informants: I use it to order food, shop online, pay for online transportation, basically the practicality of using it. (Interview 27,Zain) In line with the previous research, e-wallet is being used as a mode of transactions amongst youngsters, millennials, and generation Z altogether (Monilakshmane, 2019) (Daqar, 2020) (Persada, 2021). The main factors in using e-Wallet, namely discount (Prasasti, 2021); ease-of-use (Daqar, 2020); seemingly good idea (Persada, 2021); and the quality of mobile application (Phuong, 2020).…”
Section: Interviewer: What Is the Reason Why You Used E-wallet During The Pandemics?supporting
confidence: 57%
“…Their engagement with technology means they are open to fintech and they trust online apps. Both Generation Z and Millennials consider that fintech are cheaper than banks [110]. Young generations are expected to open their first account and do transactions with financial apps instead of traditional banks [111].…”
Section: Sampling and Data Collectionmentioning
confidence: 99%
“…A very interesting study conducted by Karsh (2020) to investigate the financial behaviour, usage intention and perception towards FinTech services of Millennials and Gen Z. The study was conducted the in Palestine and a global comparison was made to understand counter parties' viewpoint.…”
Section: Alternative Financing and Customers' Perspectivementioning
confidence: 99%